2001
DOI: 10.1046/j.1469-0705.2001.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculovascular physiology of the growth‐restricted fetus

Abstract: Growth restriction is associated with abnormal ventriculovascular physiology that represents a successful adaptive response to raised placental impedance and reduction in wall stress as evidenced by the lower fetal pulse wave velocity in growth-restricted fetuses. However, whilst fetal adaptive mechanisms may aid survival they may result in cerebral and vascular abnormalities that prejudice later cardiovascular health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 40 publications
3
44
0
1
Order By: Relevance
“…31,32 It was further observed that reduction of somatic growth in IUGR was accompanied by a reduction in the peripheral vascular bed size. 31 However, after correction for estimated fetal weight, the fetal aortic vessel diameters were found to be comparable to those of the normally grown fetuses, thus indicating that the discrepancy between body habitus and vessel size observed in our study may possibly be a phenomenon occurring after birth.…”
Section: Discussionmentioning
confidence: 96%
“…31,32 It was further observed that reduction of somatic growth in IUGR was accompanied by a reduction in the peripheral vascular bed size. 31 However, after correction for estimated fetal weight, the fetal aortic vessel diameters were found to be comparable to those of the normally grown fetuses, thus indicating that the discrepancy between body habitus and vessel size observed in our study may possibly be a phenomenon occurring after birth.…”
Section: Discussionmentioning
confidence: 96%
“…They appear to have a lower pulsewave velocity, possibly caused by stiffer arteries with decreased vessel-wall pulsations. 7,35 The pulse-wave velocity correlates with mean blood pressure and is associated with the PSVs of the cardiac outflow tracts. 7 The present finding that cardiac output and PSV are reduced in fetuses with suboptimal fetal growth is consistent with decreased pulsewave velocity in small fetuses and suggests increased afterload with raised mean arterial pressure.…”
Section: Cardiac Circulationmentioning
confidence: 99%
“…The distinction between infants who have not achieved their growth potential and have shown abnormal Doppler waveforms-usually reduced, absent, or reversed flow in the descending aorta during fetal life intrauterine growth restriction (IUGR)-and those destined to be small with normal Doppler flow profiles (SGA) is vital because the vascular influences during fetal life are different. Not only do IUGR fetuses experience direct abnormalities of vascular impedance, altering their flow patterns for sustained periods, 5,6 but they are also often exposed to potential transgenerational influences. Pregnancy complications, such as low birth weight, preterm delivery, and preeclampsia, are associated with a 7-fold increased risk of the mother requiring hospitalization or dying from ischemic heart disease within the subsequent 2 decades.…”
Section: See Article By Olander Et Almentioning
confidence: 99%